DEVELOPMENT OF MATHEMATICS STATISTICS E-MODULE ORIENTED ON SCHEMATIC REPRESENTATION - Anwar, Rahmad; Rahmawati, Dwi; Widjajanti, Kristina (MATEMATIKA DAN PEMBELAJARAN, 2024)
This development research aims to describe the development of the mathematical statistics e-module I which is oriented towards schematic representation. The development stages include needs analysis, initial product design, prototype I, validation, analysis of validation results, final product. The subjects in this study were students of the fourth semester mathematics education study program. There were 25 students in total. The instruments used in this study included expert validation sheets, lecturer and student response questionnaires. The results showed that the mathematical statistics e-module I oriented towards schematic representation, which had been developed, was rated as very valid based on the validation by expert respondents. In addition, the results of e-module development were also stated to be very practical based on lecturer and student respondents with an average of 80.9%. Based on the research results obtained, it can be concluded that the development of the mathematical statistics e-module I which is oriented towards schematic representation is very valid and practical to use and makes it easier for students to learn. Keywords: E-module; Schematic Representation; Mathematical Statistics